Stades method for surgical correction of upper eyelid trichiasis-entropion: results and follow-up in 21 cases - Laus,José Luiz (2000)
Trichiasis is a condition in which lhe cuia and facial hairs grow toward lhe córnea or the conjunctiva. The hairs arising from normal sites are pointed aí an abnormal direction. This condition may be caused by prominent nasal folds, entropion, blepharospasm, slipped facial mask and dermoids. The upper eyelid trichiasis-entropion with lower eyelid entropionectropion frequentiy occurs in oíder English Cocker Spaniels. The ocular signs often are epiphora, blepharospasm, conjunctivitis, keratitis and comeal ulceratíon. Treatment depenas on the severity ofthe condition and must eliminate the ocular contact by misdirected cuia that irritate the eyeball. This report presents a retrospective study of21 patients with bilateral diffüse trichiasis (15 English Cocker Spaniels; 2 Basset hounds; l Bloodhound; l Fila Brasileiro and 2 mongrel dogs). The procedure described by Stades was employed m ali cases. Postoperatively, topical chioramphenicol oiníment (qid) was appiied in the conjunctival soe and on the open woundfor 2 weeks. Sutures were removed 10 days after surgery. Correction ofpositioning ofthe upper eyelid was successfúl and its apposition to córnea was normal. In most of the cases the reepithelialiwtion was complete one month after surgery. No signs ofrecurrence werefound and there appeared to be no loss of normal fünction of the eyelid in the 21 dogs available for follow-up examination in a maximum period of 36 months.